2019
DOI: 10.1007/s00382-019-04998-5
|View full text |Cite
|
Sign up to set email alerts
|

Temperature domination of AMOC weakening due to freshwater hosing in two GCMs

Abstract: Anthropogenic climate change is projected to lead to a weakening of the Atlantic meridional overturning circulation (AMOC). One of the mechanisms contributing to this is ice melt leading to a freshening of the North Atlantic Ocean. We use two global climate models to investigate the role of temperature and salinity in the weakening of the AMOC resulting from freshwater forcing. This study finds that freshwater hosing reduces the strength of the AMOC, but in some situations it is not through reduced density fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 31 publications
3
20
0
Order By: Relevance
“…211 Afterward, the AMOC strength started to rapidly recover. As described in the previous 212 studies 15,43,45 , the AMOC exhibits a clear hysteresis behavior, and such behavior has critical influences on the ITCZ changes due to the alterations in the hemispheric heat distribution.…”
Section: Irreversible Itcz Responses and Global Energy Exchangesmentioning
confidence: 67%
See 1 more Smart Citation
“…211 Afterward, the AMOC strength started to rapidly recover. As described in the previous 212 studies 15,43,45 , the AMOC exhibits a clear hysteresis behavior, and such behavior has critical influences on the ITCZ changes due to the alterations in the hemispheric heat distribution.…”
Section: Irreversible Itcz Responses and Global Energy Exchangesmentioning
confidence: 67%
“…Figure 3c shows the AMOC response to the CO2 ramp-up and -down forcing. With 206 the increase in CO2, the overturning circulation was gradually weakened due to the freshening of the Arctic sea-ice decline 42 , the buoyant surface cap 43 , and surface hydrology change 44 . After the CO2 turnabout, the AMOC strength further weakened and reached its minimum value in about Year 2200, namely the AMOC overshooting (Extended Data Fig.…”
Section: Irreversible Itcz Responses and Global Energy Exchangesmentioning
confidence: 99%
“…However, the amplitude of each component may vary with intrinsic or extrinsic factors. Cycle lengths on potentially intermediate time scales ≈1000 years have been discussed by Haskins et al [20] Cycle lengths on paleontological time scales have been identified by Imbrie et al [21] and others.…”
Section: Ocean Cyclesmentioning
confidence: 93%
“…Reduction of AMOC due to freshwater input from Greenland is also observed in idealized experiments, i.e., common freshwater hosing experiments (e.g., Haskins et al 2020;Swingedouw et al 2012Swingedouw et al , 2014. These experiments are usually performed with a much stronger, unrealistic freshwater input to kick the AMOC response.…”
Section: The Oceanic Responsementioning
confidence: 96%